Diseases of the Peripheral Nervous System (Texas Journal of Medical Science, 2022)
With the rapid development of information technology in the world today, many new symptoms of many diseases are being identified. Especially in this regard, much higher results are being achieved in diseases of the nervous system. This article discusses the most common peripheral nervous system diseases and their types